Anthelmintic potential and in vivo acute toxicity study of Piptadenia gonoachanta leaf aqueous extract - Mariana Costa Fausto, Idelvânia dos Anjos Nonato, Guilherme Costa Fausto, Rogério Pinto, Fabrício Luciani Valente, Lorendane Millena de Carvalho, Artur Kanadani Campos, Marcelo Barcellos da Rosa, Jackson Vitor de Araújo , Camilo Amaro de Carvalho (Journal of Applied Pharmaceutical Science, 2017)
Piptadenia gonoacantha (Leguminosae) is an arboreal species found in southern and southeastern Brazil. Several compounds have been identified in their leaves, such as anthraquinones, phenolics, tannins, saponins, coumarins and flavonoids. The presence of these metabolites is associated with antioxidant, anti-inflammatory, antibiotic and anthelmintic properties. This study evaluated the phytochemical profile of in vitro anthelmintic activity and in vivo toxicity of the aqueous extract of P. gonoacantha leaves. The extracts were distinctly evaluated by extraction method: maceration (EAM), ultrasonication (EAU) and lyophilization (EAL). Anthelmintic activity analysis was carried out for all preparations at 25, 50 and 100 mg.mL-1 against Panagrellus sp. in an in vitro assay. In vivo toxicity was assessed by biochemical, hematological and histological evaluation of Balb/C mice treated orally with EAU (100, 200 and 400 mg.Kg-1) for 10 consecutive days. Phytochemical analysis showed the presence of tannins, flavonoids, coumarins, saponins, glycosides, phenolic compounds and anthraquinone. Anthelmintic potential showed significant results, with inhibition potential ranging from 93.93% and 99.88% among the different concentrations and preparations tested. In absolute values, the EAPG at 50 mg / mL showed a higher percentage of inhibition, reaching the following concentrations: 25, 50 and 100 mg / mL of preparation I (EAM), 25 and 100 mg / mL of preparation II (EAU) and 25 , 50 and 100 mg / mL of preparation III (EAL), had percentage of inhibition of 99.39%, 96.15%, 96.57%, 96.45%, 95.01%, 99.74% and 99% 44% respectively. EAU has proved to be safe for in vivo use because it showed low toxicity, enabling it to future pre-clinical and clinical studies.
Keywords: Anthelmintic activity,Piptadenia gonoacantha, Low toxicity,Leguminoseae.